On Agelena labyrinthica (Clerck, 1757) and some allied species, with descriptions of two new species of the genus Agelena from China (Araneae: Agelenidae) - Zhang, Zhi-Sheng; Zhu, Ming-Sheng; Song, Da-Xiang (Zootaxa, 2005)
Seven allied species of the funnel-weaver spider genus Agelena Walckenaer, 1805, including the type species Agelena labyrinthica (Clerck, 1757), known to occur in Asia and Europe, are reviewed on the basis of the similarity of genital structures. Two new species are described: Agelena chayu sp. nov. and Agelena cuspidata sp. nov. The specific name A. silvatica Oliger, 1983 is revalidated. The female is newly described for A. injuria Fox, 1936. Two specific names are newly synonymized: Agelena daoxianensis Peng, Gong et Kim, 1996 with A. silvatica Oliger, 1983, and A. sublimbata Wang, 1991 with A. limbata Thorell, 1897. Some names are proposed for these species to represent some particular genital structures: conductor ventral apophysis, conductor median apophysis, conductor distal apophysis and conductor dorsal apophysis for male palp and spermathecal head, spermathecal stalk, spermathecal base and spermathecal apophysis for female epigynum.